2013
DOI: 10.1177/0956797613492773
|View full text |Cite
|
Sign up to set email alerts
|

Shared Neural Mechanisms Underlying Social Warmth and Physical Warmth

Abstract: Many of people’s closest bonds grow out of socially warm exchanges and the warm feelings associated with being socially connected. Indeed, the neurobiological mechanisms underlying thermoregulation may be shared by those that regulate social warmth, the experience of feeling connected to other people. To test this possibility, we placed participants in a functional MRI scanner and asked them to (a) read socially warm and neutral messages from friends and family and (b) hold warm and neutral-temperature objects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
139
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(155 citation statements)
references
References 38 publications
14
139
1
1
Order By: Relevance
“…Inagaki and Eisenberger (2013) found that social warmth can make people feel physically warmer, which suggests that socially warm activities may effectively reduce physical coldness. Other research also hints at this possibility, suggesting that social warmth can be used as a buffer for physical coldness (Kolb et al, 2012;Zhou et al, 2012).…”
Section: Applying the Goal Systems Framework To Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Inagaki and Eisenberger (2013) found that social warmth can make people feel physically warmer, which suggests that socially warm activities may effectively reduce physical coldness. Other research also hints at this possibility, suggesting that social warmth can be used as a buffer for physical coldness (Kolb et al, 2012;Zhou et al, 2012).…”
Section: Applying the Goal Systems Framework To Future Researchmentioning
confidence: 99%
“…Similarly, Ijzerman and Semin (2009) found that participants seated in a warm room report feeling interpersonally closer to the experimenter than do those seated in a colder room. Conversely, experiencing social rejection makes people feel physically cold (IJzerman et al, 2012;Zhong & Leonardelli, 2008), experiencing social connection makes people feel physically warm (Hahn et al, 2012;Inagaki & Eisenberger, 2013), and thinking about a target's sociability traits increases estimates of room temperature (Szymkow et al, 2013).…”
mentioning
confidence: 99%
“…Beyond mere metaphor, a growing body of research now suggests that changes to actual physical warmth can also affect perceptions of “social warmth,” feeling loved by and connected to others. For example, after holding warm objects, participants rated another person as interpersonally warmer (Williams & Bargh, 2008), reported feeling closer to other people (IJzerman & Semin, 2009), increased their trusting behavior (Kang, Williams, Clark, Gray, & Bargh, 2011), and felt more socially connected (Inagaki & Eisenberger, 2013). While these results suggest an overlap between experiences of social and physical warmth, the mechanisms, particularly the neurochemical mechanisms, linking these two concepts are unknown.…”
mentioning
confidence: 99%
“…In addition, opioid-rich neural regions, such as the insula and ventral striatum (VS), show increased activity to innocuous physical warmth. For instance, participants asked to hold warm (vs. neutral) stimuli show increased activity in the insula (Becerra et al, 1999; Davis, Kwan, Crawley, & Mikulis, 1998; Inagaki & Eisenberger, 2013; Olausson, Charron, Marchand, Villemure, Strigo, & Bushnell, 2005; Rolls, Grabenhorst, & Parris, 2008; Verhagen, Kadohisa, & Rolls, 2004), and increases in self-reported pleasure in response to holding a warm stimulus are associated with increased ventral striatum activity (Rolls et al, 2008). …”
mentioning
confidence: 99%
See 1 more Smart Citation